2016
DOI: 10.5604/12321966.1226852
|View full text |Cite
|
Sign up to set email alerts
|

Risk exposure to vibration and noise in the use of agricultural track-laying tractors

Abstract: Human exposure to mechanical vibration may represent a significant risk factor for exposed workers in the agricultural sector. Also, noise in agriculture is one of the risk factors to be taken into account in the evaluation of workers’ health and safety. One of the major sources of discomfort for the workers operating a tractors is the noise to which they are exposed during work. The aim of this study was to evaluate the risk of exposure to whole-body vibration for the operator driving track-laying tractors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Indeed, animal studies found that exposure to continuous quantitative vibration diminished the proteoglycan content in the nucleus pulposus disrupting the integrity of the matrix and increasing the instability of the intervertebral disc [30]. The results of our study support the possibility of an association with occupational driving and of course workers in the agricultural/fishing industries may also be exposed to whole-body vibration in tractors or boats [31, 32].…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, animal studies found that exposure to continuous quantitative vibration diminished the proteoglycan content in the nucleus pulposus disrupting the integrity of the matrix and increasing the instability of the intervertebral disc [30]. The results of our study support the possibility of an association with occupational driving and of course workers in the agricultural/fishing industries may also be exposed to whole-body vibration in tractors or boats [31, 32].…”
Section: Discussionsupporting
confidence: 66%
“…In the literature, numerous studies have investigated these safety issues, mainly focusing on specific topics such as tractors' technical features: e.g., ROPS [19,30], vibrations [31], ergonomics of commands [32], etc. Other studies have analyzed injuries related to this type of equipment in specific geographical contexts [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…However, even contributing to the optimization of agricultural operations, the intensification of the use of mechanized equipment in the coffee harvesting process can expose workers to high levels of noise that, depending on the intensity and time of exposure, can compromise their occupational health (LIMA JÚNIOR et al, 2014;VALLONE et al, 2016).…”
Section: Introductionmentioning
confidence: 99%